Contemporary challenges of spatial development of local service centres in the suburban areas of Wrocław – example of Czernica, Poland - Kryczka, Piotr; Chrobak, Katarzyna (Budownictwo i Architektura / Civil and Architectural Engineering, 2020)
The residential anthropopressure in the areas around large urban centres has become an irrefutable fact. According to many analysts, the suburban development is not related to rational land-use, focused on shaping multifunctional settlement units. The paper is a study of a selected case of spatial development of a service function in the suburban area of Wrocław. The article presents the literature on the subject of building systems of service centres, as well as the analysis of planning documents of the Czernica municipality, including their correlation with higher-order planning studies. As a consequence of the above, the spatial structure of the municipality and potential development possibilities of the service centres system were analysed. For this purpose, GIS analyses (in particular, the analysis of building density or spatial accessibility analysis) were carried out. The research constituted an important starting point for shaping guidelines in the area referring to establishing a hierarchical system of service centres. This led to the further debate on shaping the spaces for integration of rural residents connected to local service centres.